2011
DOI: 10.1038/ejhg.2011.145
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic complementation of MeCP2 deficiency: phenotypic rescue of Mecp2-null mice by isoform-specific transgenes

Abstract: Rett syndrome (RTT) is a disorder that affects patients' ability to communicate, move and behave. RTT patients are characterized by impaired language, stereotypic behaviors, frequent seizures, ataxia and sleep disturbances, with the onset of symptoms occurring after a period of seemingly normal development. RTT is caused by mutations in methyl-CpG binding protein 2 (MECP2), an X-chromosome gene encoding for MeCP2, a protein that regulates gene expression. MECP2 generates two alternative splice variants encodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 30 publications
4
45
1
Order By: Relevance
“…This finding indicates that either MeCP2 splice variant is sufficient to fulfill MeCP2 function in the mouse brain (40). Our findings reveal a novel mechanism for the pathogenesis of MeCP2 mutations in extraembryonic tissue, wherein maternally inherited MeCP2_e2 mutations result in placenta abnormalities that ultimately lead to a survival disadvantage for carriers of this mutant allele.…”
Section: Maternally Transmitted Mecp2_e2 Null Allele Results In Apoptmentioning
confidence: 66%
“…This finding indicates that either MeCP2 splice variant is sufficient to fulfill MeCP2 function in the mouse brain (40). Our findings reveal a novel mechanism for the pathogenesis of MeCP2 mutations in extraembryonic tissue, wherein maternally inherited MeCP2_e2 mutations result in placenta abnormalities that ultimately lead to a survival disadvantage for carriers of this mutant allele.…”
Section: Maternally Transmitted Mecp2_e2 Null Allele Results In Apoptmentioning
confidence: 66%
“…The concept on the importance of MeCP2E2 isoform in RTT is strengthened by the ability of Mecpe2e2 expression alone to rescue RTT phenotypes in mice (Luikenhuis et al 2004;Jugloff et al 2008), which also indicates that Mecp2e2 is required and able to maintain normal brain functions. However, the efficiency of the rescue of RTT phenotypes differs between the two Mecp2 isoforms, where Mecp2e1 is more efficient in rescuing RTT phenotypes than Mecp2e2 (Kerr et al 2012). Together, these reports highlight that even though, the exon 1 mutations are found in rare cases of RTT and no mutations are found in exon 2, both MECP2 isoforms seem to be affected in Rett syndrome patients.…”
Section: Presence Of Mutations and Relevance To Rttmentioning
confidence: 93%
“…Independent research groups have shown that introduction of MeCP2 into RTT mouse models can rescue the phenotypes. Interestingly, both MeCP2 isoforms can rescue the RTT phenotypes to different extents, where MeCP2E1 application is more successful as expression of Mecp2e1 alone can rescue RTT phenotypes (Kerr et al 2012). However, other studies show that expression of Mecp2e2 alone can prevent the disease progression in Mecp2 null mouse models (Luikenhuis et al 2004;Giacometti et al 2007;Jugloff et al 2008).…”
Section: Rescue Of Rtt Phenotypesmentioning
confidence: 99%
“…Two (P225R and P322L) involve proline residues and therefore potentially disrupt the overall fold of the protein. A third (A2V) affects only one of the two known MeCP2 isoforms 11,12 , and data regarding the importance of the residues specific to this isoform are conflicting 21, 103,104 . Some studies have detected isoform-specific functions 104 , whereas others have argued that the functional significance of the few differing amino acids are subtle or absent 21,103 .…”
Section: Human Mutations Underlying Disease Pathologymentioning
confidence: 99%